Composite Practically Fixed Time Controller Design for a Hypersonic Vehicle With Multisource Uncertainty and Actuator Fault - Wang, Fang; Li, Yaping; Zhou, Chao; Zong, Qun; Hua, Changchun (IEEE transactions on aerospace and electronic systems, 2021)
This article addresses the tracking control problem of a hypersonic vehicle subject to multisource uncertainty and actuator fault. A composite fixed time control scheme is designed to achieve the stable tracking of velocity and altitude in fixed time. A nonsingular fast terminal sliding mode controller and a practically fixed-time backstepping controller are, respectively, developed for velocity subsystem and altitude subsystem. Fixed-time disturbance observer is used to tackle lumped uncertainties and a new fast fixed time filter is constructed to avoid the “explosion of terms” problem. Then, the fixed-time stability of velocity tracking error and the practically fixed-time stability of altitude tracking error are proved. Finally, compared simulations are carried out to present the efficiency of the designed control scheme.